Konstruksi Pemahaman Masyarakat Terhadap Hadis "Kullu Bid'atin Dlalalah" - Mu'awwanah, Nafisatul (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2016)
This article discusses the problems of bid’ah in society. The problems originated from differences in the public’s understanding of the hadis kullu bid’atin dlalalah. Such defferences include the definition of bid’ah, bid’ah classification, and the methods used to judge the practices that are not practiced by Rasulullah, companions, and scholars of the Salaf. The situation often cause conflicts in society. To solve this problem, Peter L. Berger gave some solution by theory of social contruction. This theory told us that the problems of bid’ah are caused by three processes, there are eksternalitation, objectivation, and internalitation. And the problems can be solved by two processes, there are institusionalitation and socialization.Key Word: Bid’ah, Hadis, Sosial Contruction.